1999
DOI: 10.1253/jcj.63.196
|View full text |Cite
|
Sign up to set email alerts
|

Left Ventricular End-Systolic Wall Stress is a Potent Prognostic Variable in Patients With Dilated Cardiomyopathy

Abstract: Dilated cardiomyopathy is an important cause of morbidity and mortality among patients with heart failure. Left ventricular dilation is viewed as a compensatory response to maintain stroke volume, and left ventricular dilation is directly related to the increase of wall stress. However, only a few studies have examined whether wall stress can be a prognostic variable in patients with dilated cardiomyopathy. This study was designed to elucidate whether left ventricular systolic wall stress was related to the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 27 publications
(29 reference statements)
1
8
0
1
Order By: Relevance
“…We previously reported that left ventricular end-systolic wall stress is a potent prognostic variable in patients with DCM, 21 and in that study, left ventricular end-systolic wall stress and ES of Tl-201 scintigraphy were significantly positively correlated. 21 Doi et al 11 and Shiotani et al 12 reported that the severity of Tl-201 perfusion defects in patients with DCM is associated with a poor prognosis.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…We previously reported that left ventricular end-systolic wall stress is a potent prognostic variable in patients with DCM, 21 and in that study, left ventricular end-systolic wall stress and ES of Tl-201 scintigraphy were significantly positively correlated. 21 Doi et al 11 and Shiotani et al 12 reported that the severity of Tl-201 perfusion defects in patients with DCM is associated with a poor prognosis.…”
Section: Discussionsupporting
confidence: 54%
“…21 Doi et al 11 and Shiotani et al 12 reported that the severity of Tl-201 perfusion defects in patients with DCM is associated with a poor prognosis. Bukley et al 22 indicated that constant perfusion defects seen on thallium scans in patients with DCM might represent areas of myocardial fibrosis and scarring.…”
Section: Discussionmentioning
confidence: 99%
“…To maintain cardiac output, wall stress is increased, and, to compensate, the heart enlarges and becomes more spherical, a physical manifestation of the Laplace principle. 11 This principle appears to underlie our results, which show that the circle index was significantly lower in patients with DCM than in healthy individuals. In healthy individuals, the angle between the tangential lines was largest at the apex, and the shape became elliptical.…”
Section: Circle Index and Hemodynamicsmentioning
confidence: 51%
“…2 Hara et al noted that an increase in the noncontractile region of myocardial tissue may be related to an increase in left ventricular diameter. 11 This would explain the correlation between the circle index and LVD. We found the circle index useful for evaluating change in elliptical shape over time in DCM.…”
Section: Circle Index and Hemodynamicsmentioning
confidence: 97%
“…The utility of end-systolic wall stress and the stress-adjusted velocity in pediatric patients has been demonstrated in those with sickle-cell anemia, anthracycline exposure, and various forms of congenital heart disease and arrhythmia [28][29][30]. LV end-systolic wall stress is predictive of outcome in adult patients with DCM [31].…”
Section: Wall Stress and Measurement Of Afterloadmentioning
confidence: 99%